A Novel Method for Determining Link Correlation and Candidate Key in VANETs (International Journal of Engineering and Computer Science, 2017)
A Collection of optimal relaying node in an intra-street and excellent of the eventually street at the intersection are the dominant challenging issues merit to its valuable mobility and uneven selection of vehicles in social Vehicular Adhoc NETworks (VANETs). In this paper , the probability of link availability can be estimated by a standardize model which considers the stable and unstable vehicle states. In an existing work, the periodic route discovery message broadcasting increases the delay in path establishment. A new concept called the link correlation which represents the influence of different link combinations in network topology. The link correlation concept is applied to transmit a packet with less network resource amount and higher profitable put. Based on link correlation, an opportunistic routing metric is designed as the assignment guidance of a relaying node in intrastreets and it is called as Expected Transmission Cost around a multi-hop Path (ETCoP). This opportunistic routing metric can further provide use for the next street selection at an intersection. Ultimately, a street-centric opportunistic routing protocol is considered based on ETCoP (SRPE) for VANETs. Forwarding candidate selection technique based on velocity vector is contributed to recover the performance.